ANALISIS BIAYA-VOLUME-LABA DALAM MEREALISASIKAN TARGET PENJUALAN MASSA BODI KERAMIK BATU PADA BTIKK TAHUN 2018 - I Nyoman Normal (Forum Manajemen STIMI Handayani Denpasar, 2019)
The aims of this research were: (1) To know the Break-Even Point; (2) To determine the margin of safety; and (3) To realize target profit by decreasing offixed cost, decreasing of unit variable cost, increasing of sales price, and increasing of mixed unit sales. The research results shew that: (1) The Break-Even Point of that stoneware compositions was 5.852,12 kg that followed by 2.926,06 kg for BL-1, 877,82 kg for BL-3, 1.345,99 kg for BPC-1, 409,65 kg for BSK-1, and 292,61 kg for BNK-2 or Rp 35.087.830,04 each month, that followed by BL-1 Rp 18.141.562,46, BL-3 Rp 5.047.450,85, BPC-1 Rp 7.806.723,97, BSK-1 Rp 2.365.718,27, and BNK-2 Rp 1.726.374,49; (2) The Margin of Safety for that stoneware compositions was 2,46%, and (3) The cost-volume-profit analysis is used to plan sales of that stoneware composition. Net profit planning about Rp 167.671,48 each month at the present sales about 4.000,00 kg can acted by four ways, that is: decreasing fixed cost about Rp 2.267.622,23, decreasing unit variable cost Rp 572,16 for BL-1, Rp 573,64 for BL-3, Rp 552,88 for BPC-1, Rp 565,08 for BSK-1, and Rp 561,21 for BNK-2, increasing of sales price Rp 450,00 for BL-1, Rp 624,24 for BL-3, Rp 729,26 for BPC-1, Rp 743,24 for BSK-1, and Rp 570,26 for BNK-2, and increasing of unit sales about 995,00 kg for BL-1, 294,50 kg for BL-3, 465,00 kg for BPC-1, 145,20 kg for BSK-1, and 100,00 kg for BNK-2.